AHP and CLD as Pre-Research Tools for Strategic ESG-Based Competency Models: A Resource-Based View in Action - Saratian, Eko Tama Putra; Akbar, Taufik; Suparno; Mukhtar, Saparuddin (Jurnal Informatika Ekonomi Bisnis, 2025)
This study proposes an integrated pre-research framework using the Analytic Hierarchy Process AHP and Causal Loop Diagrams CLD to model strategic ESG-based competencies within the context of Islamic banking, grounded in the Resource-Based View RBV. As ESG considerations increasingly become critical to organizational performance and competitive advantage, especially for value-driven institutions such as Islamic banks, early-stage modeling is essential for identifying key resources and dynamic interactions. AHP is employed to prioritize critical competencies such as crisis response, ESG integration, and innovation based on expert judgment, while CLD is used to visualize feedback structures linking these competencies to sustainable competitive advantage and strategic business performance. The findings demonstrate how AHP and CLD can complement each other in refining theoretical frameworks by combining quantitative prioritization with qualitative system dynamics. This hybrid approach not only enhances conceptual clarity and model robustness but also serves as a diagnostic foundation before empirical validation. The framework offers significant implications for strategic planning in ESG-sensitive industries, contributing methodologically to RBV applications and practically to ESG adoption in Islamic banking.